Development of a computer program to simulate the predictions of the replaced elements model of Pavlovian conditioning (2007)
Despite of the apparent simplicity of Pavlovian conditioning, research on its mechanisms has caused considerable debate, such as the dispute about whether the associated stimuli are coded in an «elementistic» (a compound stimuli is equivalent to the sum of its components) or a « configural» (a compound stimuli is a unique exemplar) fashion. This controversy is evident in the abundant research on the contrasting predictions of elementistic and the configural models. Recently, some mixed solutions have been proposed, which, although they have the advantages of both approaches, are difficult to evaluate due to their complexity. This paper presents a computer program to conduct simulations of a mixed model (replaced elements model or REM). Instructions and examples are provided to use the simulator for research and educational purposes. Copyright © 2007 Psicothema.